STUDY OF COMPLEX STRUCTURAL GENRES IN THE WORK OF ALISHER NAVOI (Konferensiyalar | Conferences, 2024)
The article focuses on poetic genres that are relatively rare in Uzbek classical literature, and draws the scientific conclusion that they have a complex structure. The authors studied modern views in Uzbek literature, got acquainted with the works of such scientists as A. Hayitmetov, Yo.Iskhakov, R. Orzibekov, A.Qayumov, F. Nabiev, D. Yusupova, M. Asadov and gave their assessment in terms of genre requirements in order to come to this conclusion. According to the authors, complex structural genres are actively found in classical literature, in the work of Alisher Navoi. The article analyzes the tarkibbands of Navoi, identifies their poetic features, considers the creativity of the poet based on the requirements of the genre, gives scientific conclusions about the possibility of creating a system of complex genres. In contrast to the works created up to that time, the article applies the term of complex structural genres to the genres of Navoi’s works such as sokinoma, mughanniynoma, tarjiband, tarkibband, masnavi-noma, musammat, and analyzes them through a single scientific system. In this system, the tarkibband and sokinoma are shown as active genres, and their specific features are also demonstrated.